PENGEMBANGAN APLIKASIKONVERSI MATA KULIAH MENGGUNAKAN FRAMEWORKCODEIGNITER DAN BOOTSTRAP (Studi Kasus : Sekolah Tinggi Ilmu Komunikasi Profesi Indonesia) - Abu Sopian (Universitas Mohammad Husni Thamrin, 2018)
Students who enroll in the Sekolah Tinggi Ilmu Komunikasi Profesi Indonesia are not only from High School Graduates or from the same level. But students who enroll are also available from Bachelor Degree (D3) or called Level Transfer. For that, it is necessary to do equalization or conversion of courses from Bachelor Degree (D3). Currently the conversion of subjects in still done manually. Forthat, it is necessary to develop an application that can help in converting for subject. In this study the development of course conversion applications is used Software Development Life Sycle (SDLC) method with the waterfall model. Based on the analysis of the system design above, it can be concluded that the Model View Controller (MVC) architecture can be applied to the codeigniter framework and MVCarchitecturemaking it easier to repair changes to the source code without changing the entire logic and fungtion properly and meet the objectives the beginning of the development of this subject conversion application.